Characterization of Epichloë coenophiala within the US: are all tall fescue endophytes created equal? - Young, Carolyn A.; Charlton, Nikki D.; Takach, Johanna E.; Swoboda, Ginger A.; Trammell, Michael A.; Huhman, David V.; Hopkins, Andrew A. (Frontiers in Chemistry, 2014)
Tall fescue (Lolium arundinaceum) is a valuable and broadly adapted forage grass that occupies approximately 14 million hectares across the United States. A native to Europe, tall fescue was likely introduced into the U.S. around the late 1800’s. Much of the success of tall fescue can be attributed to Epichloë coenophiala (formerly Neotyphodium coenophialum) a seed borne symbiont that aids in host persistence. Epichloë species are capable of producing a range of alkaloids (ergot alkaloids, indole-diterpenes, lolines and peramine) that provide protection to the plant host from herbivory. Unfortunately, most tall fescue within the U.S., commonly referred to as KY31, harbors the endophyte E. coenophiala that causes toxicity to grazing livestock due to the production of ergot alkaloids. Molecular analyses of tall fescue endophytes have identified four independent associations, representing tall fescue with E. coenophiala, Epichloë sp. FaTG-2, Epichloë sp. FaTG-3 or Epichloë sp. FaTG-4. Each of these Epichloë species can be further distinguished based on genetic variation that equates to differences in the alkaloid gene loci. Tall fescue samples were evaluated using markers to SSR and alkaloid biosynthesis genes to determine endophyte strain variation present within continental U.S. Samples represented seed and tillers from the Suiter farm (Menifee County, KY), which is considered the originating site of KY31, as well as plant samples collected from 14 states, breeder’s seed and plant introduction lines (National Plant Germplasm System, NPGS). This study revealed two prominent E. coenophiala genotypes based on presence of alkaloid biosynthesis genes and SSR markers and provides insight into endophyte variation within continental U.S. across historical and current tall fescue samples.